2012
DOI: 10.1002/mds.25126
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of oral betamethasone to reduce ataxia symptoms in ataxia telangiectasia

Abstract: No controlled studies exist regarding the pharmaceutical reduction of ataxia symptoms in ataxia telangiectasia (A-T). In a multicenter, double-blind, randomized, placebo-controlled crossover trial, oral betamethasone (BETA) and placebo were compared in terms of their reduction of ataxia symptoms as assessed with the International Cooperative Ataxia Rating Scale (ICARS). In this study of 13 A-T children, betamethasone reduced the ICARS total score by a median of 13 points in the intent-to-treat population and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Third, more research concerning the measurement and treatment of childhood ataxia is needed. There are few reports specific to children regarding the measurement 37 and treatment of ataxia (pharmacologic [38][39][40][41][42] and nonpharmacologic [43][44][45] ). This may reflect the fact that the overall prevalence and importance of childhood ataxia has likely been underestimated in the past, despite the fact that ataxia is associated with significant economic cost and decreased quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Third, more research concerning the measurement and treatment of childhood ataxia is needed. There are few reports specific to children regarding the measurement 37 and treatment of ataxia (pharmacologic [38][39][40][41][42] and nonpharmacologic [43][44][45] ). This may reflect the fact that the overall prevalence and importance of childhood ataxia has likely been underestimated in the past, despite the fact that ataxia is associated with significant economic cost and decreased quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Ataxia scores (SARA) improved in all patients at the dosage of 0.03 mg/kg/day [63]. In a double-blind, randomized, placebo-controlled crossover trial, oral betamethasone (0.1 mg/kg/day for 2×10 days with 10 days intermediate tapering) improved ataxia assessed by ICARS by 17 points (about 30 %) compared to placebo (improvement of 4.5 points) (Table 3) [64]. However, minimal dosage, long-term effectiveness, and safety need to be established.…”
Section: Drug Therapy For Cerebellar Ataxiamentioning
confidence: 99%
“…Even though steroids are not curative and cannot be proposed for long-term therapies due to their side effects, it is suggested that during the clinical course there is a phase when neurological impairment can be rescued to some extent 56. In a multicenter, double-blind, randomized, placebo-controlled, crossover trial, oral betamethasone use showed significant reduction in ataxia scores 57. Dexamethasone has been shown to induce a splicing event, which leads to the skipping of mutations upstream of nucleotide residue 8450 of the ATM coding sequence.…”
Section: Role Of Atm In Neuroprotectionmentioning
confidence: 99%